PELAYANAN PERIZINAN SURAT IZIN USAHA PERDAGANGAN PADA DINAS PENANAMAN MODAL PELAYANAN TERPADU SATU PINTU - Harapan Tua R.F.S, Zulmei Akhirisya, Meyzi Heriyanto, (Jurnal Ilmu Administrasi Negara, 2019)
Licensing Services for Trading Business Licenses at the One-stop IntegratedInvestment and Services Office. This study aims to determine the licensing services one-stopservice permit for the city of Pekanbaru. The research method is qualitative. Research informantswere the Head and Secretary of the Pekanbaru DPMPTSP Office, Head of District, communityservice employees and entrepreneurs. Data collection techniques are interviews and observation.Data analysis through data reduction procedures, data presentation and conclusion drawing. Theresults showed that the licensing service for issuing permits and extending SIUP permits inPekanbaru City DPMPTSP can be seen from the attitude of employees who are very responsive inserving the people who come to them, the officers try to know the desires and wishes of serviceusers.